2015
DOI: 10.1259/bjr.20140811
|View full text |Cite
|
Sign up to set email alerts
|

Using the CT features to differentiate invasive pulmonary adenocarcinoma from pre-invasive lesion appearing as pure or mixed ground-glass nodules

Abstract: The authors Jing Liang and Xiao-quan Xu contributed equally to this article.Objective: To differentiate pre-invasive lesion from invasive pulmonary adenocarcinoma (IPA) appearing as ground-glass nodules (GGNs) using CT features. Methods: 149 GGNs were enrolled in this study, with 74 pure GGNs (p-GGNs) and 75 mixed GGNs (m-GGNs). Firstly, univariate analysis was used to analyse the difference of CT features between pre-invasive lesion and IPA. Then, multivariate analysis was conducted to identify variables that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 34 publications
(50 reference statements)
2
38
1
Order By: Relevance
“…Furthermore, the foci of fibrosis would become larger with the increased invasive grade of tumor. This mechanism suggests that pleural indentation is significantly associated with invasive extent., which is consistent with the findings of Takashima et al [18] and Liang et al [19] on mixed GGN.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the foci of fibrosis would become larger with the increased invasive grade of tumor. This mechanism suggests that pleural indentation is significantly associated with invasive extent., which is consistent with the findings of Takashima et al [18] and Liang et al [19] on mixed GGN.…”
Section: Discussionsupporting
confidence: 94%
“…In a similar study performed by Lee et al [10], they found that lesion size was the sole predictor of invasive extent. Moreover, Liang et al [19] demonstrated that the amount of blood vessels ( n ≥ 1) was also an independent risk factor able to differentiate IPAs from preinvasive lesions. Based on these results, we incorporated more variables compared to previous prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, central fibrosis and the resultant tissue contraction could cause fibrotic strands around the tumor, which were recognized on CT as pleural indentations . Moreover, the foci of fibrosis would become larger when the malignancy probability of a nodule increased . Furthermore, serum tumor markers are associated with malignancy, and CEA has been demonstrated as an effective marker for a wide range of malignancies .…”
Section: Discussionmentioning
confidence: 99%
“…21 Moreover, the foci of fibrosis would become larger when the malignancy probability of a nodule increased. 22 Furthermore, serum tumor markers are associated with malignancy, 23 and CEA has been demonstrated as an effective marker for a wide range of malignancies. 24 Although the serum CEA level was associated with smoking and age, 25 the multivariate analysis indicated serum CEA as a significant rather than the confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…AIS and MIA have a (near) 100% disease-free survival after resection and usually grow slowly [ 27 ]. Several studies have investigated which morphological features would allow for differentiating pre-invasive from invasive nonsolid lesions [ 15 , 28 ]. More research would be beneficial to reveal more insight in predictive morphological features of pre-invasive and invasive nonsolid nodules.…”
Section: Discussionmentioning
confidence: 99%